Mitochondria-Associated Membranes: a platform for transferring endoplasmic reticulum stress signals to mitochondria in innate immune cells. Does lithium promote an adaptive cellular response and survival? - Pascale, Jessica De (2019)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia